2002
DOI: 10.1183/09031936.02.00281602
|View full text |Cite
|
Sign up to set email alerts
|

The rapamycin analogue SDZ RAD attenuates bleomycin-induced pulmonary fibrosis in rats

Abstract: Pulmonary fibrosis is characterized by excessive deposition of extracellular matrix proteins within the pulmonary interstitium. The new macrolide immunosuppressant SDZ RAD, a rapamycin analogue, inhibits growth-factor dependent proliferation of mesenchymal cells and might therefore be of therapeutic interest for the treatment of fibrotic lung disease.In this study the effect of SDZ RAD on lung-collagen accumulation in the bleomycin model of pulmonary fibrosis in rats was investigated. SDZ RAD (2.5 mg?kg -1 ?da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 19 publications
7
59
0
1
Order By: Relevance
“…The dose of everolimus tested in the study is based on the dose used in topical applications of everolimus in experimental keratoplasty [27], and it is far less than the dose used to elicit immunosuppressive effects in rats (1.0 to 3.0 mg/kg/day Table 2. Histological assessment of fibrosis and inflammation in the lamina propria of tympanic membranes orally) [16][17][18]25]. The hypothesis was confirmed:…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The dose of everolimus tested in the study is based on the dose used in topical applications of everolimus in experimental keratoplasty [27], and it is far less than the dose used to elicit immunosuppressive effects in rats (1.0 to 3.0 mg/kg/day Table 2. Histological assessment of fibrosis and inflammation in the lamina propria of tympanic membranes orally) [16][17][18]25]. The hypothesis was confirmed:…”
Section: Discussionsupporting
confidence: 53%
“…Everolimus has been reported to inhibit fibroblast proliferative capabilities and to reduce lung-collagen accumulation in bleomycin-induced pulmonary fibrosis [25]. Everolimus-coated coronary stents have been shown to effectively prevent intimal hyperplasia following stent implantation and to control restenosis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition to immunosuppressive effects, rapamycin also showed to be effective in preventing fibrogenesis in animal models. [11][12][13] However, the exact molecular mechanisms underlying the effects of rapamycin on preventing organ fibrosis remain poorly understood. Furthermore, the antifibrotic effect of rapamycin was seriously challenged by other studies, which showed that rapamycin had no significant improvements on fibrotic process.…”
mentioning
confidence: 99%
“…Liu et al, 1993), Ginkgo biloba (Daba et al, 2002;Iraz et al, 2006), Moxibustion (R. Li et al, 2005), Fufang (Kong et al, 2005) etc. ), Immunosuppressants (Cyclosporin-A (Lossos, Or, Goldstein, Conner, & Breuer, 1996), Rapamycin analogue SDZ RAD (Simler et al, 2002)), Corticosteroids (Dexamethasone (F. Chen et al, 2006;Dik et al, 2003;H. P. Li, Li, He, Yi, & Kaplan, 2004), Methylprednisolone (Phan, Thrall, & Williams, 1981), Prednisolone (Chaudhary, Schnapp, & Park, 2006;Entzian et al, 1998) 1986) etc.…”
Section: Drug Intervention Studies In the Bleomycin Modelmentioning
confidence: 99%
“…Pirfenidone early (Schelegle, Mansoor, & Giri, 1997) Decorin early (Shimizukawa et al, 2003) 16 7 SDZ RAD early (Simler et al, 2002) 16 8…”
Section: Idmentioning
confidence: 99%